The Joy of birds: the effect of rating for joy or counting garden bird species on wellbeing, anxiety, and nature connection - Maria E. White; Iain Hamlin; Carly W. Butler; Miles Richardson (Urban Ecosystems, 2023)
The feeding of garden birds is a popular and accessible means of connecting with wildlife in urban environments in the United Kingdom. Past research has found that the main motivations for feeding birds are psychological benefits, concern for bird welfare, and connecting to nature. This study explores whether a brief birdwatching activity impacts on wellbeing, anxiety, and nature connection. One hundred and fifty-six participants took part in a birdwatching activity, identifying the species that entered their garden during a thirty-minute period. Participants were randomly allocated to the ‘joy’ group, who rated their feeling of joy on seeing each species, or the ‘count’ group, who counted the number of birds of each species. Measures of wellbeing, state anxiety and nature connection were completed before and after the observation period. Both groups had improved wellbeing, anxiety, and nature connection, though decreases in anxiety were greatest for those in the joy group. These results suggest that activating a sense of joy heightens the psychological benefits of watching garden birds. These benefits and the strengthening of nature connections highlight the reciprocal relationship between humans and birds and the importance of actions towards healthy, sustainable urban ecosystems.